Interview with Vyacheslav V. Ivanov about semiotics, the languages of the brain and history of ideas - Velmezova, Ekaterina; Kull, Kalevi (Sign Systems Studies, 2011)
The interview with one of the founders of the Tartu–Moscow school, semiotician Vyacheslav Vsevolodovich Ivanov (b. 1929) from August 2010, describes V. V. Ivanov’s opinions of several scholars and their work (including Evgenij Polivanov, Mikhail Bakhtin, Andrej Kolmogorov, Nikolaj Marr etc.), his relationships with his father Vsevolod Ivanov, as well as V. V. Ivanov’s views on the past and future of semiotics, with some emphasis on neurosemiotics, zoosemiotics, semiotics of culture, cybernetics, history of linguistics, study and protection of small languages. The interview also deals with V. V. Ivanov’s book Even and Odd.